É golpe?: metáforas conceptuais do impeachment da Presidente Dilma - Pinheiro, Cynthia Gomes (2019)
ABSTRACT Metaphor is a cognitive mechanism that allows us to conceptualize our everyday experiences. This research aimed to investigate how the impeachment of President Dilma Rousseff, occurred in 2016, was conceptualized in the speeches of representatives of Brazilian society, based on conceptual metaphors that were used in the construction / understanding of this concept. Specifically, our objectives were to analyze the cultural / ideological values that supported the conceptual metaphors evidenced, as well as to verify the existence of specific metaphors that categorize the impeachment of 2016. The corpus of our work is constituted by pronouncements of participants of the judgment occurred in the Federal Senate that compose the books "20 hours in history: the long session of admissibility of the Impeachment of President Dilma Rousseff" and "Impeachment: the judgment of President Dilma Rousseff by the Federal Senate", as well as comments and opinions of ordinary people and public people about the topic in question, taken from newspapers, magazines and blog sites. We used as theoretical reference the Theory of Conceptual Metaphor (TCM), studied by Lakoff and Johnson (1987, 1999, 2002 [1980], 2003), Lakoff and Turner (1989) and Kövecses (2000, 2010 [2002], 2005), and the notion of Idealized Cognitive Model (MCI), according to Lakoff (1987). In order to analyze the relationship between metaphor, culture and ideology, we use the postulates of Kövesces (2005) and Goatly (2007). The hypothesis that the conceptualization of President Dilma's impeachment can be investigated from the conceptual metaphors that reflect two antagonistic political-ideological positions in Brazilian society, namely, one opposite and the other favorable to impeachment, was demonstrated by the qualitative analysis of the data. In the results found from the investigated corpus, we observed the use of two groups of source domains that structure the concept of impeachment and that consolidate, each of them, the macro metaphors IMPEACHMENT IS BLOW and IMPEACHMENT IS NOT BLOW, conceptualizing the impeachment of President Dilma Rousseff negatively and positively, respectively.